Evaluasi Pembelajaran PKn Berbasis Nilai dalam PKn di MI - Rosmawati, Rosmawati (Yayasan Zia Salsabila, 2022)
This study aims to evaluate the implementation of value-based learning in Pancasila and Citizenship Education (PPKn) in Madrasah Ibtidaiyah (MI). Value-based learning is expected to strengthen students' understanding of citizenship values including rights and obligations, democracy, and national and state life. The method used is a qualitative approach with a case study design, involving in-depth interviews with teachers and students, as well as observations of the learning process in the classroom. Data analysis was carried out using thematic analysis techniques to identify key themes related to the implementation and impact of value-based learning. The results of the study indicate that value-based learning has a positive impact on students' understanding of basic citizenship concepts, but its effectiveness is limited by factors such as uneven educational infrastructure, teacher skills in using learning technology, and students' difficulties in understanding abstract concepts. The implications of this study are the importance of improving the quality of teaching and educational infrastructure to support the optimal implementation of this method. This study recommends the need for teacher training and improving educational facilities to strengthen value-based learning in MI.